Analysis of Sigli Syariah Court Judges' Opinion On Ex-Husband's Marriage During Their Ex-Wife's Iddah Period - Sukiati, S; Yazid, Imam; Irfan, Muhammad (Alhurriyah, 2024)
This research aims to answer the analysis of the Sigli Syariah Court Judge's views on Circular Letter of BIMAS Ministry of Religious Affairs of Indonesia (Surat Edaran BIMAS Islam Kementerian Agama RI) on Marriage During the Wife's Iddah Period. In 2021, the Islamic Community Guidance of the Indonesian Ministry of Religion issued Circular Letter Number: P-005/DJ.III/Hk.00.7/10/2021 concerning Marriage During the Wife's Iddah Period. In the provisions of letter E number 3 of the Circular Letter, it is stipulated that a man's ex-husband can marry another woman after his ex-wife's iddah period has been completed because it is feared that covert polygamy will occur. Interestingly, in the statutory provisions, there are no provisions relating to the prohibition on a man's ex-husband marrying another woman while he is still in his ex-wife's iddah period. This research is empirical legal research with a qualitative approach, and data collection in this research uses observation, interview techniques, and then analysis. This research found that, in Islamic law, there is no provision for an iddah period for men, and a man does not have to wait for the end of his ex-wife's iddah period if he wants to marry another woman. Sigli Syariah Court Judge argued that the Circular Letter No. P-005/DJ.III/Hk.00.7/10/2021 is in line with the al-maslahah al-ammah theory because it contains beneficial values and aims to avoid hidden polygamy. The value of the benefits contained in the circular letter will be properly realized if formal laws are followed.